Group Counseling Innovation: Self-Management Techniques for Enhancing Discipline Among Vocational High School Students - Sari, Mustika; Netrawati (Universitas Ahmad Dahlan, 2025)
The issue of students' lack of discipline in public schools remains a major challenge in educational institutions. When disciplinary issues such as tardiness, failure to complete homework, skipping classes, and truancy are left unaddressed, they can disrupt the learning process and directly impact students' academic performance. This study aims to analyze the improvement of learning discipline among vocational high school students (SMKN) using behavioristic group counseling with self-management techniques to enhance student discipline. The research employed a quantitative approach with an experimental method. The design used in this study was a quasi-experimental design. The sample consisted of 195 students, from which 10 students were selected for the experimental group and 10 students for the control group, all of whom exhibited low levels of learning discipline. The sampling technique used was simple random sampling. Data analysis techniques included the Wilcoxon Signed Rank Test and the Kolmogorov-Smirnov 2 Independent Samples test. The findings revealed that group counseling services using a behavioristic 1approach with self-management techniques effectively improved students' learning discipline. These results provide practical implications for school counselors in delivering guidance and counseling services, particularly group counseling services, using a behavioristic approach with self-management techniques to systematically improve students' learning discipline.